Mapping of Physical-Water Attributes in an Oxisol Under Sugarcane Cultivation in Ceres Municipality, Goiás State (GO), Brazil - Silva, Isabela Larissa Alves; Machado, Roriz Luciano; Santana, Patriky Rangel Leal; Compagnon, Ariel Muncio (International journal of Rural Development, Environment and Health Research, 2023)
This paper aimed to determine and spatialize physical-hydric attributes in the sugarcane area at the Sugarcane Research Unit in Ceres (GO) in Cerrado (vegetation of the Brazilian interior),. The experiment comprised an area of 285 x 60 m with a 15 m sampling grid, in which a deformed and undisturbed soil sampling was carried out from January 2020 to January 2021. The evaluated attributes were: (a) clay ; (b) sand; (c) silt; (d) soil density (SD); (e) particle density (PD); (f) total porosity (TP); (g) macroporosity (macro); (h) microporosity (micro); (i) water retention in field capacity (FC); (j) water retention in the permanent wilting point (PWP); and (k) total water availability (TWA). All physical attributes showed moderate to strong spatial dependence with adjustments to Gaussian models predominantly for granulometry and exponential, and spherical for the others, ranging from 15.4 to 191.9 m. Results of TWA spatial variability allow defining two management units and show that the soil under study has low water retention in the available water range. This study provides information that enables decision-making in irrigation management and soil decompaction..